A Trajectory towards a Culture of Quality: A Phenomenological Study of an Open Distance Learning University in South Africa and in China - Kershnee Sevnarayan (Research in Social Sciences and Technology, 2022)
Over the past few years we have witnessed immense advancements of technology which challenge conventional teaching methodologies. Through an international staff exchange program that was attended over a period of two weeks, this paper compares two distance education universities from two culturally diverse continents; Africa and Asia, more specifically, a distance university in China and an open distance and e-Learning university in South Africa. This paper focuses on supporting students through quality assurance by reflecting on both distance-learning institutions and generated data by means of field notes and observations that took place during presentations. It is argued that effective and quality teaching and learning cannot occur without tightened quality control measures in a course. Arguably, if teaching and learning is quality controlled, success and throughput rates would improve. The findings in this paper indicate that an enabling environment that caters for quality assurance activities to be implemented on a continuous basis needs to be effected. Distance learning institutions need to move towards a culture of quality and by doing this they need to tailor their student support not just to produce graduates at end of a cohort but to produce quality graduates needed for the ever-evolving and rapidly transforming information and communication technologies. This paper concludes with recommendations for distance education institutions to move towards a trajectory of a culture of quality. It is argued that an environment that is conducive for quality assurance activities is needed for an effective culture of quality to ensue.